Functionalized cellulose beads with activated carbon Fe3O4/CoFe2O4 for cationic dye removal - Moosavi, Seyedehmaryam; Gan, Sin Yee; Zakaria, Sarani (Editura Academiei Romane, 2019)
Modified regenerated cellulose beads functionalized with activated carbon (AC), as well as magnetic cellulose beads of AC-Fe3O4 and AC-CoFe2O4, were synthesized. The AC was further used as adsorbent for the removal of cationic methylene blue (MB) dye from aqueous solution. The magnetic cellulose beads possessed a high magnetic response to an external magnetic field and their ease of recovery could be facilitated with the aid of a magnetic field. The synthesized adsorbents were characterized using a Field Emission Scanning Electron Microscope (FESEM), as well as by energy dispersive X-ray (EDX) spectrometry and thermogravimetric analysis (TGA). In comparison with the synthesized magnetic cellulose beads, the maximum adsorption capacity of the adsorbent beads assisted with AC, AC-Fe3O4 and AC-CoFe2O4 was of 54, 53 and 50 mg/g, respectively. The kinetic study of the adsorption of MB dye onto the adsorbents was performed at different parameters (initial dye concentration and temperature). The kinetics of the adsorption fit well with the pseudo-second-order model. © 2019 Editura Academiei Romane. All rights reserved.